Interstrain differences in the severity of liver injury induced by a choline- and folate-deficient diet in mice are associated with dysregulation of genes involved in lipid metabolism - Tryndyak, Volodymyr (Federation of American Societies for Experimental Biology, 2012)
Nonalcoholic fatty liver disease (NAFLD) is a major health problem and a leading cause of chronic liver disease in the United States and developed countries. In humans, genetic factors greatly influence individual susceptibility to NAFLD. The goals of this study were to compare the magnitude of interindividual differences in the severity of liver injury induced by methyl-donor deficiency among individual inbred strains of mice and to investigate the underlying mechanisms associated with the variability. Feeding mice a choline- and folate-deficient diet for 12 wk caused liver injury similar to NAFLD. The magnitude of liver injury varied among the strains, with the order of sensitivity being A/J ≈ C57BL/6J ≈ C3H/HeJ < 129S1/SvImJ ≈ CAST/EiJ < PWK/PhJ < WSB/EiJ. The interstrain variability in severity of NAFLD liver damage was associated with dysregulation of genes involved in lipid metabolism, primarily with a down-regulation of the peroxisome proliferator receptor α (PPARα)-regulated lipid catabolic pathway genes. Markers of oxidative stress and oxidative stress-induced DNA damage were also elevated in the livers but were not correlated with severity of liver damage. These findings suggest that the PPARα-regulated metabolism network is one of the key mechanisms determining interstrain susceptibility and severity of NAFLD in mice.—Tryndyak, V., de Conti, A., Kobets, T., Kutanzi, K., Koturbash, I., Han, T., Fuscoe, J. C., Latendresse, J. R., Melnyk, S., Shymonyak, S., Collins, L., Ross, S. A., Rusyn, I., Beland, F. A., Pogribny, I. P. Interstrain differences in the severity of liver injury induced by a choline- and folate-deficient diet in mice are associated with dysregulation of genes involved in lipid metabolism.